Presence of women in Geology in Cuban Scientific Journals from the study of its scientific production - Figueredo Figueredo, Ana Luisa (2017)
In the research is deals with the results of the study on the presence of women in Geology in Cuban scientific journals during the period 1968 to April 2016, based on an analysis of their scientific production related to Geology. It was studied and taken data from the National Serial Publications Register of Cuba, to select the Cuban scientific journals whose lines of research are related to Geology. The women were identified from an uprising of the members of the Cuban Society of Geology and bibliometric techniques (counting and analysis) were applied from which productivity indicators were determined (productivity per year, by authors and the most represented themes)Were identified 54 geologists, with a total of 103 scientific articles on Geology, located in 8 publications. Among the main results it had that the productivity of the geologists in Cuban scientific journals has remained irregular since its beginning and that the quality and relevance of each of the publications are endorsed by journals indexed in databases of international recognition. It concludes with the need to strengthen the presence of women in Geology in Cuban scientific journals, taking into account the value of their contributions to society.